There is need a new insight for celiac disease - Usta, Yusuf (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Usta Y. There is need a new insight for celiac disease. Turk J Gastroenterol 2018; 29: 149-50.